Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Pemerintahan (Studi Kasus pada Instansi Pemerintah Kota Batu) - Likuwatan, Mayatisari; Malikah, Anik; Mawardi, M. Cholid (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study was to find out how the influence of the Accounting Information System and Internal Control System on Government Performance "Case Study of Batu City Government Agencies". The variables used in this study consist of independent variables: Accounting Information Systems and Internal Control Systems. Dependent variable: Government Performance. This research was conducted from March to completion at Batu City Government Agencies. The population of this study are employees of Batu City Government Agencies. The sample in this study amounted to 49 employees using a purposive sampling technique. The data used in this study is primary data using a questionnaire. The analytical method used is multiple regression equation, normality test, classical assumption test, descriptive statistical analysis and hypothesis testing. The results of the study show that simultaneously the Accounting Information System and the Internal Control System have a positive and significant effect on Government Performance. While partially the Accounting Information System has no significant positive effect on Government Performance and the Internal Control System has a significant positive effect on Government Performance.Keywords: Accounting information systems, internal control systems, government performance.